Algebra Examples

Factor x^4-16
x4-16
Step 1
Rewrite x4 as (x2)2.
(x2)2-16
Step 2
Rewrite 16 as 42.
(x2)2-42
Step 3
Since both terms are perfect squares, factor using the difference of squares formula, a2-b2=(a+b)(a-b) where a=x2 and b=4.
(x2+4)(x2-4)
Step 4
Simplify.
Tap for more steps...
Step 4.1
Rewrite 4 as 22.
(x2+4)(x2-22)
Step 4.2
Factor.
Tap for more steps...
Step 4.2.1
Since both terms are perfect squares, factor using the difference of squares formula, a2-b2=(a+b)(a-b) where a=x and b=2.
(x2+4)((x+2)(x-2))
Step 4.2.2
Remove unnecessary parentheses.
(x2+4)(x+2)(x-2)
(x2+4)(x+2)(x-2)
(x2+4)(x+2)(x-2)
x4-16
(
(
)
)
|
|
[
[
]
]
7
7
8
8
9
9
4
4
5
5
6
6
/
/
^
^
×
×
>
>
1
1
2
2
3
3
-
-
+
+
÷
÷
<
<
π
π
,
,
0
0
.
.
%
%
=
=
 [x2  12  π  xdx ]